2023
DOI: 10.1039/d3gc01506h
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Cu0–Cu+ sites by Pb-doping for highly efficient CO2 electroreduction to C2 products

Abstract: The electrochemical CO2 reduction reaction (CO2RR) can convert CO2 to C2 hydrocarbons and oxygenates over Cu-based catalysts, which has great potential to store renewable energy and close the carbon cycle....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Therefore, it is suggested that the unique flower-like micro/nanostructure of Cu-F-M and Cu-F catalysts may not only provide a larger electrochemically active surface area but also induce the formation of CuNPs@Cu(110) surface structures during electrochemical activation, thereby improving CO 2 conversion and increasing selectivity to specific products (e.g., ethanol) in the eCO 2 RR. , As a result, the Cu-F-M catalyst exhibits a significantly higher selectivity of C 2+ products (including ethanol) in the eCO 2 RR (Figure b), in comparison to the Cu-P-M catalyst. On the other hand, previous studies have highlighted the key role of Cu + species in enhancing *CO adsorption and C–C coupling to facilitate the generation of C 2+ products in the eCO 2 RR. Interestingly, despite both the collapse of flower-like morphology and the absence of Cu + species (Figures S9 and S11) on the spent Cu-F-M after stability evaluation, the spent Cu-F-M electrocatalyst with remaining CuNPs@Cu(100) surface structures (Figures S12–14) still exhibits high ethanol selectivity. The above results sufficiently demonstrate that CuNPs@Cu(100) surface structures in the Cu-F-M catalyst play a decisive role in promoting the production of C 2+ products in the eCO 2 RR.…”
Section: Resultsmentioning
confidence: 94%
“…Therefore, it is suggested that the unique flower-like micro/nanostructure of Cu-F-M and Cu-F catalysts may not only provide a larger electrochemically active surface area but also induce the formation of CuNPs@Cu(110) surface structures during electrochemical activation, thereby improving CO 2 conversion and increasing selectivity to specific products (e.g., ethanol) in the eCO 2 RR. , As a result, the Cu-F-M catalyst exhibits a significantly higher selectivity of C 2+ products (including ethanol) in the eCO 2 RR (Figure b), in comparison to the Cu-P-M catalyst. On the other hand, previous studies have highlighted the key role of Cu + species in enhancing *CO adsorption and C–C coupling to facilitate the generation of C 2+ products in the eCO 2 RR. Interestingly, despite both the collapse of flower-like morphology and the absence of Cu + species (Figures S9 and S11) on the spent Cu-F-M after stability evaluation, the spent Cu-F-M electrocatalyst with remaining CuNPs@Cu(100) surface structures (Figures S12–14) still exhibits high ethanol selectivity. The above results sufficiently demonstrate that CuNPs@Cu(100) surface structures in the Cu-F-M catalyst play a decisive role in promoting the production of C 2+ products in the eCO 2 RR.…”
Section: Resultsmentioning
confidence: 94%
“…[40][41][42] Currently, a wide range of products has been produced through diverse reaction systems, including CO, formic acid, CH 4 , CH 3 OH, ethylene, ethane, ethanol and other C 2+ products. [43][44][45][46][47] As is shown in Figure 1B, after being absorbed onto electrode surface, the CO 2 molecule is then transformed into CO 2 ˙− or * CO intermediates over different electrode materials. 48 These two intermediates could directly desorb from the electrode to yield the 2-electron transfer products, CO and HCOOH.…”
Section: Electroreduction Of Co 2 To Chemicals and Fuelsmentioning
confidence: 99%
“…31,32 Previous work proposed the significance of localized interface bonding between active sites and support, facilitating the stabilization of highly reactive, coordinatively unsaturated cations. 25,29−31 Especially, some studies have incorporated pblock metals such as Gd, 33 Pb, 34 and Sn 35 to stabilize Cu + species, significantly improving CO 2 reduction performance. Among various supports, silicon (Si) oxide stands out for its exceptional ability to stabilize reaction intermediates and transition states, courtesy of its influence on solvent dynamics.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In Cu-based catalyst, the reactivity and catalytic efficacy are profoundly influenced by the structural and chemical attributes of the surface and interfaces, which are the primary locales for CO 2 electroreduction. When CuO x are juxtaposed onto the other oxides, the resulting oxide–oxide interface markedly impacts their structural integrity and catalytic behavior. , Previous work proposed the significance of localized interface bonding between active sites and support, facilitating the stabilization of highly reactive, coordinatively unsaturated cations. , Especially, some studies have incorporated p-block metals such as Gd, Pb, and Sn to stabilize Cu + species, significantly improving CO 2 reduction performance. Among various supports, silicon (Si) oxide stands out for its exceptional ability to stabilize reaction intermediates and transition states, courtesy of its influence on solvent dynamics.…”
Section: Introductionmentioning
confidence: 99%